On the Development of Working with Personnel in Forensic Organizations under the Requirements of the International Standard ISO/IEC 17025:2017 - E. V. Chesnokova (Теория и практика судебной экспертизы, 2020)
The purpose of the study is to adapt the requirements of the international standard ISO/IEC 17025: 2017 “General requirements for the competence of testing and calibration laboratories”, defining the functions and responsibilities of laboratory personnel, to the domestic forensic expert activity. The following requirements for personnel are addressed in the article: impartiality, competence, manageability, and performance of operations according to the laboratory’s management system. International standards and comments to them, foreign forensic practice, publications on domestic forensic expert science, and procedural codes of the Russian Federation have been analyzed. The article points out that in forensic organizations, the entire staff divides into two groups: those who perform forensic examinations (research) and those who ensure the functioning of the forensic organizations. Achieving objectivity in laboratory activities during research or testing is strictly applicable and is regulated by documenting the research/ test, validating research/test methods, training and admitting personnel, and maintaining equipment. The combination of these procedures ensures the objectivity of a study. It is shown that the standard extends its provisions to all accredited organizations under the uniform rules, which goes along with the ethical standards of the forensic expert institutions of the Ministry of Justice of the Russian Federation, other departments, as well as commercial organizations.